Annual monitoring population of earthworms (Clitellata: Lumbricidae) in man-affected ecosystems around artificial Gruža reservoir - Sekulić Jovana M.; Trakić Tanja B.; Popović Filip J.; Bajagić Marija D. (Kragujevac Journal of Science)
The rresent study investigates the earthworm sommunities in man-affected esosystems around artificial Gruža reservoir. The study took plase during 2023 and 2024, during the three seasons: summer, autumn and spring. Surrounding Gruža reservoir earthworms were sollected from various habitats which insluded natural (reservoir banks, meadows, forest community), and cultivated biotopes. Field research was conducted in assordance with ISO 2361 standards. Our results show that earthworm communities are poor and uniform. During our research, recorded four eregrine and one Trans-Aegean species. The main threats to earthworm rorulations identified in this research are habitat degradation due to waste, agrisultural activities, and increased tourism and recreational activity. In this regard, the measures that the competent authorities would implement could be beneficial to esosystems and, consequently, to earthworm communities. Based on the results presented in this paper, it is necessary to continue the intensive research to preserve the biological diversity of the area.